2019
DOI: 10.1016/j.enpol.2019.03.040
|View full text |Cite
|
Sign up to set email alerts
|

The profitability of transnational energy infrastructure: A comparative analysis of the Greenstream and Galsi gas pipelines

Abstract: This paper explores how the profitability of European transnational gas infrastructure is affected by (i) alternative ways to organize the gas supply chain; and (ii) different forms of energy diplomacy. In particular, through a case study, the paper analyses how these factors determined the realisation and success of the Greenstream pipeline and the stalemate of the Galsi pipeline, despite the potential for both projects to be profitable. The issue is important in view of the full transition to the EU Single M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…[13] indicates the use of a government-to-government mechanism in the energy sector to promote projects. This is also found in the Nord Stream 2 project as economic and supply benefits attributed to political support from Germany and Austria, tied to economic and supply benefits [14], and the Green Stream pipeline that benefited from close diplomatic relations between Libya and Italy [15]. This support extends to transit countries, as found by [16].…”
Section: Literature Reviewmentioning
confidence: 75%
See 3 more Smart Citations
“…[13] indicates the use of a government-to-government mechanism in the energy sector to promote projects. This is also found in the Nord Stream 2 project as economic and supply benefits attributed to political support from Germany and Austria, tied to economic and supply benefits [14], and the Green Stream pipeline that benefited from close diplomatic relations between Libya and Italy [15]. This support extends to transit countries, as found by [16].…”
Section: Literature Reviewmentioning
confidence: 75%
“…This support extends to transit countries, as found by [16]. Conversely, an unstable political climate between stakeholders can negatively impact pipelines, as found in Indian pipeline projects [17][18][19] and the Galsi project [15]. A study by [6] found that 'the Nabucco consortium's biggest failure probably was that it drew up a gas pipeline infrastructure without the participation of key producer countries'.…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…This issue is important in view of the recent progress in the EU energy policy reforms, which envision a full transition to models based on short-term transactions in spot markets. In fact, in an energy-deprived area such as Europe, the full reliance on models based on short-term transactions is likely to increase the bargaining power of non-EU exporters, potentially threatening energy security and price affordability for consumers (Cardinale 2019). The fact that the transition to renewable gas will not guarantee energy independence suggests the need to carefully monitor the collateral changes that accompany the low carbon transition, especially for what concerns commercial relations between exporters and importers and their respective bargaining power.…”
Section: Energymentioning
confidence: 99%